Correction: Insecticide resistance to permethrin and malathion and associated mechanisms in Aedes aegypti mosquitoes from St. Andrew Jamaica. - Sheena Francis; Karla Saavedra-Rodriguez; Rushika Perera; Mark Paine; William C Black; Rupika Delgoda (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0179673.].